Digital labour platforms and migrant workers: Analysing migrants' working conditions and (over)representation in platform work in Europe - Wouter Zwysen; Agnieszka Piasna (European Trade Union Institute (ETUI), 2024)
Working for labour platforms is still relatively rare, but the generally poor working conditions and the impact on the world of work are the subject of much debate. Although data are scarce, there is a general consensus that migrants are overrepresented in this type of work. Platforms may well provide migrants with work opportunities, especially shortly after arrival, due to relatively lower entry barriers, including formal requirements, compared to the traditional economy. However, the entry of these more vulnerable groups into a segment of generally poor quality jobs poses serious challenges in terms of their potential exploitation and the longer-term negative effects on labour market integration and prospects. The extent to which platforms rely on migrants and create the conditions for exploitation compared to other workers is an important question with clear policy implications. However, a lack of representative data has thus far limited understanding of the extent of migrants' involvement in platform work and their working conditions in relation to non-migrant groups. This paper addresses this gap by analysing the presence of migrants and their work patterns in the European platform economy, using representative cross-national data for 14 European Union Member States collected in 2021. The analysis has three main objectives. First, it reveals the extent to which migrants are indeed overrepresented in platform work and whether this holds for different types of platform. Secondly, it explores whether there are substantial differences between migrant and non-migrant platform workers in their experiences with the platform economy in terms of earnings, hours worked and the use of one or several platforms (multi-apping). Third, by focusing on variations between migrants with different characteristics, it sheds some, primarily indirect, light on the mechanisms that guide migrants towards platform work.
Keywords: 330; Employment services; Digital services; Migrant workers; Working conditions; EU countries; Arbeitsvermittlung; Digitale Dienste; Arbeitsmigranten; Arbeitsbedingungen; EU-Staaten